Test of quality of shrimp postlarvae in commercial hatcheries: a case study - Hernández, Crisantema; Voltolina, Domenico; Rojas, Pablo; Nieves, Mario (HIDROBIOLÓGICA, 2017)
Three characteristic of postlarvae of Litopenaeus vannamei Boone which are used as indicators of postlarvae quality, were evaluated and compared as tools for internal quality control at a commercial hatchery in Ecuador, using organisms of four successive ages from each of forty different larval cultures. The results indicated that Vibrio concentration and resistance to withstand osmotic stress at any given age were not relayed, and provided little or no information to evaluate future quality in terms of survival to the point of sale test of resitance to osmotic stress. Low size variability may be used as indicative of a probable better survival to the osmotic stress test but cannot be used quantitatively as a predictive tool.